Base abandonments by low-cost carriers. (August 2016) - Malighetti, Paolo; Paleari, Stefano; Redondi, Renato
Abstract: This paper is the first attempt to systematically investigate the phenomenon of base abandonments by low-cost carriers (LCCs) in the world, from 1997 to 2014. Our results identify 109 cases where the LCCs decreased their presence in airports by at least 50 per cent in terms of offered seats. In 28 cases, the LCCs completely abandoned the airports. The incidence of downsizing is significantly reduced for important base airports. The abandonment by LCCs can be reversed, even though this is not very likely; in only 7.3 per cent of cases the same LCCs recovered full capacity. The impact on airports of LCC abandonments depends on the carrier level of dominance. The presence of middle size alternative airports increases the likelihood of downsizings. Highlights: We find 109 cases where the LCCs decreased their presence in airports by at least 50 per cent. The incidence of downsizing is significantly reduced for important base airports. In only 7.3 per cent of cases the same LCCs recovered full capacity. The impact of LCC downsizing on airports depends on the carrier level of dominance. The presence of middle size alternative airports increases the likelihood of downsizings.